Excitation energy transfer in optochemotronic emitter with modified electrodes - Жолудов, Юрий Тимофеевич (Eastern-European Journal of Enterprise Technologies, 2010)
The paper is devoted to the problem of excitation energy localization at biradical recombination reaction in optochemotronic emitter with working electrode, modified with electrochemiluminophore molecules film by means of Langmuir-Blodgett technique.